Heterosexual Plots and Lesbian Narratives. - Farwell, Marilyn (Cutting Edge: Lesbian Life and Literature Series., 1996)
What is lesbian literature? Must it contain overtly lesbian characters, and portray them in a positive light? Must the author be overtly (or covertly) lesbian? Does there have to be a lesbian theme and must it be politically acceptable?. Marilyn Farwell here examines the work of such writers as Adrienne Rich, Marion Zimmer Bradley, Jeanette Winterson, Gloria Naylor, and Marilyn Hacker to address these questions. Dividing their writings into two genres--the romantic story and the heroic, or quest, story, Farwell addresses some of the most problematic issues at the intersection of literature, se.